BUSINESS STRATEGY TO INCREASE COMPETITIVE ADVANTAGE IN THE ERA OF COVID-19 ON AL AMIN’S SHARIA LIFE INSURANCE: BUSINESS STRATEGY TO INCREASE COMPETITIVE ADVANTAGE IN THE ERA OF COVID-19 ON AL AMIN’S SHARIA LIFE INSURANCE - septiatin, Aziz; Pebrianti, Tutik (Journal Of Islamic Ekonomic and Business, 2022)
AbstractThe Covid-19 pandemic has had an impact on the insurance industry, namely the decline in insurance premiums. The most severe decline in insurance premiums occurred in the life insurance industry. This study aims to analyze the survival strategy of Al Amin's Sharia Life Insurance business in the face of the Covid-19 pandemic. This study uses a qualitative descriptive research method. Sources of data obtained from interviews with the Leadership and Marketing Manager of Sharia Life Insurance Al Amin Palembang Branch. Data analysis techniques used in this research are data reduction, data presentation and conclusions. The results showed that the business strategies carried out by Al Amin Sharia Life Insurance Palembang Branch in dealing with Covid-19 were first, analyzing market conditions, second, carrying out marketing strategies, namely with a professional and personal approach, third, product diversification, and fourth, pattern specifically, namely rate adjustment and limit expansion. The obstacles faced in running the business are that all decisions of Al Amin Sharia Life Insurance Palembang Branch are at the head office, constraints on personal approaches, and rate reductions or adjustments. Keywords: Business survival strategy, Life Insurance, marketing strategy